Composition for catalytic cracking catalyst, catalytic cracking catalyst as well as preparation method and application of catalytic cracking catalyst

Through the composition of rare earth modified Y-type molecular sieve and REUSY molecular sieve and sodium-lowering modification treatment, the problems of complex catalyst preparation process and insufficient product performance are solved, and the catalyst's high activity, stability and low coke effect are achieved.

CN119259106APending Publication Date: 2025-01-07PETROCHINA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310812512.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing catalytic cracking catalyst preparation process is complicated, resulting in a decrease in the yield of gasoline and liquefied gas in the product, and there are problems such as high sulfate, low crystallinity, equipment corrosion, long production process and high cost.

Method used

The composition of rare earth modified Y-type molecular sieve, binder, matrix material and REUSY molecular sieve is controlled by homogenization, molding and sodium reduction modification treatment to control the SO42- content not more than 1 wt% to improve the activity and stability of the catalyst. and heavy oil conversion capability.

Benefits of technology

It significantly improves the activity, stability and heavy oil conversion ability of the catalyst, inhibits the formation of contaminated coke, and has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent resistance to heavy metals and low coke.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004320374350000211
    Figure BDA0004320374350000211
  • Figure BDA0004320374350000271
    Figure BDA0004320374350000271
  • Figure BDA0004320374350000281
    Figure BDA0004320374350000281
Patent Text Reader

Abstract

The invention relates to the field of catalysts, and discloses a composition for a catalytic cracking catalyst, the catalytic cracking catalyst and a preparation method and application of the catalytic cracking catalyst. The composition comprises a rare earth modified Y type molecular sieve, a binder, a matrix material, a rare earth element source and an optional REUSY molecular sieve, and the content of SO4 < 2-> in the rare earth modified Y type molecular sieve is not greater than 1wt%. The catalytic cracking catalyst prepared from the composition provided by the invention has the characteristics of high activity, good stability, strong heavy oil conversion capability, excellent heavy metal resistance and low coke content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a catalytic cracking catalyst composition, a catalytic cracking catalyst, and a preparation method and application thereof. Background Art

[0002] As the main means of reducing the weight of heavy oil to light oil, catalytic cracking occupies an important position in my country, with a processing capacity of more than 200 million tons. In order to improve the economic benefits of the unit and realize the "full use" of crude oil resources, it is often necessary to increase the proportion of residual oil blending in the unit. Residual oil usually contains high levels of heavy metals such as V, which easily form vanadic acid during the catalytic cracking process, resulting in permanent destruction of the molecular sieve structure of the catalyst's active component, resulting in a decrease in the heavy oil conversion capacity and the formation of polluted coke. At the same time, as the largest source of carbon emissions in refineries, catalytic cracking units directly or indirectly emit a large amount of greenhouse gases. Carbon emission control of catalytic cracking units has become a key research topic in the petrochemical industry. Therefore, it is urgent to develop heavy metal-resistant and low-coking heavy oil catalytic cracking catalysts to reduce carbon emissions from catalytic cracking units.

[0003] The existing technology of heavy metal resistant catalysts generally involves adding heavy metal resistant matrix during the molding process, designing a metal coating on the carrier, or preparing heavy metal resistant additives. CN202010203656.9 discloses a heavy metal pollution resistant catalytic cracking catalyst and its preparation method and application, and relates to a heavy metal pollution resistant catalytic cracking catalyst, the catalytic cracking catalyst has a core-shell structure, the core-shell structure includes a core containing catalytic cracking catalyst finished particles, and a shell containing rare earth metal oxides. The catalytic cracking catalyst of the present invention has good anti-heavy metal vanadium pollution effect, and when it is used in the catalytic cracking process of high vanadium raw oil, the conversion rate of raw oil is high, and the selectivity of dry gas and coke is low. CN1073614C discloses a method for preparing a rare earth-containing hydrocarbon cracking catalyst resistant to vanadium poisoning, the method is to precipitate a mixed rare earth solution with a precipitant selected from ammonia, ammonium hydrogen phosphate or ammonium phosphate, ammonium carbonate or a mixture thereof, mix it with a carrier slurry and a molecular sieve slurry, and then spray dry it to form. The method is simple in process, and the resulting catalyst has good vanadium poisoning resistance. CN1223403C discloses a novel matrix type heavy metal resistant FCC catalyst and its preparation method. The catalyst contains 20-80m% clay, 5-40m% binder, 1-25m% metal capture component (such as rare earth oxalate), 0-30m% other oxides (such as activated alumina), 5-40m% selected from faujasite zeolite, ZSM-5 zeolite, beta zeolite or a mixture thereof with a unit cell constant of 2.432-2.472nm. The catalyst has excellent heavy metal resistance and is suitable as a catalyst for cracking heavy oil with high content of Ni, V, etc. CN201210420981.6 discloses a metal collector and its preparation method and application, wherein the metal collector contains magnesium oxide, aluminum oxide and phosphorus aluminum additive, and at least part of the magnesium oxide and at least part of the aluminum oxide form a magnesium aluminum spinel structure, wherein the bulk density of the metal collector is 0.85-1.2g / cm3. CN201110100491.3 discloses a silicon-supported lanthanum carbonate microsphere anti-vanadium additive for use in the heavy oil catalytic cracking process and a preparation method thereof. When it is used in the heavy oil catalytic cracking process in the form of an additive, it can reduce the poisoning effect of vanadium in the feed oil on the catalyst in the system, improve the conversion efficiency and the yield of light hydrocarbons and have a low coke yield.

[0004] Existing technologies have a certain effect on capturing heavy metal V and inhibiting its destruction of the active components of molecular sieves. However, there are also problems such as complicated preparation process, dilution of the cracking activity of the main agent, and reduced yield of high-value products such as gasoline and liquefied gas in the product. Y-type molecular sieve is still the main active component of FCC catalyst due to its unique three-dimensional pore structure, suitable acidity and good stability. Its performance determines the activity, stability, heavy oil conversion performance, heavy metal resistance and product selectivity of the catalyst. NaY molecular sieve itself is not acidic and usually needs to be exchanged to remove its Na ions and adjust its acidity and pore structure. The commonly used modification method is to use ammonium salts and / or rare earths for exchange, and prepare modified REHY or REUSY molecular sieves with different acidity and pore structures through thermal or hydrothermal roasting. At present, the preparation methods of REHY or REUSY molecular sieves can be roughly divided into two categories: one is to first exchange a small amount of rare earth ions and / or ammonium ions with NaY molecular sieves, and then carry out rare earth ion and / or ammonium ion or dealumination treatment after calcination to make REUSY molecular sieve; the other is to first make NaY molecular sieve into USY molecular sieve, and then exchange rare earth to prepare REUSY.

[0005] CN200610087535.2 discloses a method for preparing a REY molecular sieve. The NaY molecular sieve is contacted with an aqueous solution containing rare earth ions or with an aqueous solution containing rare earth ions and a solution or colloid containing aluminum ions, and then contacted with an external precipitant to precipitate part of the rare earth on the molecular sieve, and then subjected to hydrothermal treatment, and finally contacted with an ammonium salt aqueous solution, so that the prepared molecular sieve has a strong vanadium resistance.

[0006] CN200710121664.3 provides a catalytic cracking catalyst, containing 10-50% by weight of REY molecular sieve on a dry basis, 10-40% by weight of inorganic oxide binder on an oxide basis, and 10-70% by weight of clay on a dry basis; wherein the REY molecular sieve is prepared by the following method: after contacting the NaY molecular sieve with an aqueous solution containing rare earth ions or with an aqueous solution containing rare earth ions and a solution or colloid containing aluminum ions, contacting with an external precipitant to precipitate part of the rare earth on the molecular sieve, then performing hydrothermal treatment, and finally contacting with an ammonium salt aqueous solution, wherein the precipitant is an alkaline aqueous solution. The catalyst of the invention has a strong heavy oil cracking ability, a high gasoline yield, and a strong ability to resist vanadium pollution.

[0007] CN201511020519.7 provides a method for preparing a modified Y-type molecular sieve, which comprises exchanging the NaY molecular sieve with an ammonium salt, mixing a compound containing a IIIB element in the periodic table after filtering, spray drying and hydrothermal roasting without washing, and then exchanging with an ammonium salt, adding a precipitant or a precipitant and a filter aid, and performing or not performing hydrothermal roasting after filtering. In the preparation process of the Y-type molecular sieve according to the method of the present invention, the IIIB element is basically not lost, the exchange slurry is easy to filter, the molecular sieve yield is high, and it has excellent activity, hydrothermal stability and resistance to heavy metal pollution.

[0008] CN201280056377.8 discloses a method for ion exchange on zeolite. The invention relates to an improved method for exchanging sodium ions in a zeolite containing sodium ions and rare earth metal ions for ammonium ions. For this exchange, aqueous solutions of ammonium salts such as ammonium sulfate, ammonium nitrate or ammonium chloride are currently used. The resulting "ammonium zeolites" are calcined to convert them into H-form zeolites suitable for use as catalysts, while releasing ammonia. According to the present invention, it is proposed to use ammonium carbonate instead of the ammonium compounds mentioned. In contrast to nitrates, sulfates or chlorides, because excess ammonium carbonate can be recycled in the form of carbon dioxide and ammonia, the amount of salt that has to be discharged can be significantly reduced. The use of ammonium carbonate also minimizes the amount of rare earth metal ions leached from zeolites containing rare earth metal ions.

[0009] Effect of pre-exchange process on the modification process of Y-type molecular sieve, Biochemical Engineering, 2019, 5(1): 87-90, Wu Chuanbo proposed a new process for Y-type molecular sieve exchange and washing, and analyzed and discussed the composition and properties of the molecular sieve before and after the new process. The results showed that after the pre-exchange process, the Na + 、SO4 2- The content is significantly reduced, and the rare earth utilization rate, the crystallinity of the first calcination, and the pore volume and specific surface area of ​​the finished molecular sieve are significantly increased.

[0010] In the study of preparing LaY molecular sieve by liquid-solid combined exchange method, Zhou Xueyan et al. used magnesium hydroxide to precipitate rare earth for 5 hours, and then prepared LaY molecular sieve by solid phase exchange method by high temperature calcination, which improved the exchange degree.

[0011] In the prior art, rare earth and ammonium salt are exchanged at the same time, and the exchange efficiency is low due to the competitive exchange; ammonium salt exchange is carried out before rare earth exchange, and the use of ammonium chloride and ammonium nitrate will cause problems such as high cost and equipment corrosion, while the use of low-cost recyclable ammonium sulfate requires a large amount of water washing to remove sulfate ions to avoid the formation of sulfate precipitation, which will increase water consumption. After the rare earth modified molecular sieve is hydrothermally calcined, it is inevitable that some rare earths cannot be located in the sodalite cage, so that ammonium sulfate exchange is used in the subsequent period, resulting in the formation of rare earth sulfate precipitation, resulting in an increase in molecular sieve sulfate ions and a decrease in crystallinity. Although pre-exchange can reduce the sodium oxide and sulfate ions of the modified molecular sieve, it has the problems of long process, water consumption and high cost. REY molecular sieves prepared without ammonium salts have the problem of high coke generation.

[0012] In short, the existing technology inevitably brings problems such as high sulfate, low crystallinity, equipment corrosion, long production process and high cost. Therefore, it is urgent to develop a new method for preparing low-sulfate metal ion molecular sieves to improve the activity, stability and heavy oil conversion capacity of catalytic cracking catalysts, and avoid the conversion of sulfate into sulfide during application, which will corrode the equipment. Summary of the invention

[0013] The purpose of the present invention is to overcome the problems existing in the prior art, such as the complicated catalyst preparation process, dilution of the cracking activity of the main agent, and reduction in the yield of high-value products such as gasoline and liquefied gas. Provided are a catalytic cracking catalyst composition, a catalytic cracking catalyst, and a preparation method and application thereof. The catalytic cracking catalyst prepared using the composition has excellent heavy metal pollution resistance and coke selectivity.

[0014] The first aspect of the present invention provides a composition for a catalytic cracking catalyst, the composition comprising: a rare earth modified Y-type molecular sieve, a binder, a matrix material, a rare earth element source, and optionally a REUSY molecular sieve, wherein in the rare earth modified Y-type molecular sieve, SO4 2- The content is not more than 1wt%.

[0015] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:

[0016] (1) homogenizing, shaping, and third calcining a slurry containing the catalytic cracking catalyst composition of the present invention to obtain a catalyst precursor;

[0017] (2) The catalyst precursor is modified by reducing sodium to obtain the catalytic cracking catalyst.

[0018] The third aspect of the present invention provides a catalytic cracking catalyst prepared by the method for preparing the catalytic cracking catalyst described in the second aspect of the present invention.

[0019] The fourth aspect of the present invention provides use of the catalytic cracking catalyst of the present invention in catalytic cracking of heavy oil.

[0020] Through the above technical solution, the present invention has at least the following beneficial effects:

[0021] (1) The components of the composition of the present invention interact with each other, significantly improving its activity, stability and heavy oil conversion capacity; on the other hand, since the independent phase rare earth material on the outer surface of the rare earth modified Y-type molecular sieve can preferentially react with heavy metals, such as V, to form heavy metal acid rare earth, thereby effectively protecting the molecular sieve crystal structure and inhibiting the formation of contaminated coke;

[0022] (2) The catalytic cracking catalyst prepared using the composition of the present invention has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance and low coking. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The term "optionally" used in the present invention refers to whether the subsequent material is present or absent, and whether the subsequent operation occurs or not.

[0025] In the present invention, unless otherwise specified, "first", "second" and "third" do not indicate a sequence or limit the materials or steps, but are only used to distinguish that they are not the same steps or materials. For example, "first" and "second" in "first roasting" and "second roasting" are only used to indicate that they are not the same roasting.

[0026] The "drying" involved in the present invention is a conventional operation method in the art, and can be dried under normal pressure or under vacuum conditions, generally dried at normal pressure and 80-120° C. for 8-36 hours.

[0027] The room temperature involved in the present invention is "15-25°C".

[0028] The first aspect of the present invention provides a composition for a catalytic cracking catalyst, the composition comprising: a rare earth modified Y-type molecular sieve, a binder, a matrix material, a rare earth element source, and optionally a REUSY molecular sieve, wherein in the rare earth modified Y-type molecular sieve, SO4 2- The content is not more than 1wt%.

[0029] The rare earth element source in the present invention refers to a raw material that can provide rare earth elements.

[0030] The inventors of the present invention have found through research that the rare earth material in the catalyst prepared from the composition of the present invention can preferably form heavy metal acid rare earth with heavy metals, such as V, thereby effectively protecting the molecular sieve crystal structure and inhibiting the formation of contaminated coke. The catalyst has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance and low coke generation when used.

[0031] According to a preferred embodiment of the present invention, the rare earth element source is calculated by the weight of rare earth oxide, and the composition comprises: 15-35 wt% of rare earth modified Y-type molecular sieve, 0-20 wt% of REUSY molecular sieve, 6-30 wt% of binder, 30-55 wt% of matrix material, and 0.5-4 wt% of rare earth element source. The catalyst prepared by the composition under the aforementioned embodiment has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance, and low coke generation when used.

[0032] According to a particularly preferred embodiment of the present invention, the rare earth element source is calculated by the weight of rare earth oxide, and the composition comprises: 18-27 wt% of rare earth modified Y-type molecular sieve, 8-15 wt% of REUSY molecular sieve, 8-25 wt% of binder, 35-45 wt% of matrix material, and 0.8-3 wt% of rare earth element source. The catalyst prepared using the composition under the aforementioned embodiment has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance, and low coke generation when used.

[0033] According to a preferred embodiment of the present invention, in the rare earth modified Y-type molecular sieve: not more than 0.5wt%, for example, 0.01wt%, 0.1wt%, 0.2wt%, 0.27wt%, 0.3wt%, 0.32wt%, 0.41wt%, 0.45wt%, 0.5wt%, or the range of any two of the above values, preferably 0.01-0.45wt%. The catalyst prepared using the composition under the aforementioned embodiment has better stability and metal utilization, and when using it for catalytic cracking, it has excellent resistance to heavy metals and low coking effects.

[0034] According to a preferred embodiment of the present invention, in the rare earth modified Y-type molecular sieve: the sodium content is not more than 1.5wt% in terms of Na2O, for example, 0.2wt%, 0.5wt%, 0.62wt%, 0.82wt%, 0.92wt%, 0.98wt%, 1.1wt%, 1.2wt%, 0.5wt%, or a range consisting of any two of the above values, preferably 0.5wt%-1.2wt%. The catalyst prepared using the composition under the aforementioned embodiment has better stability and metal utilization, and when used for catalytic cracking, it has excellent heavy metal resistance and low coke generation effects.

[0035] According to a preferred embodiment of the present invention, in the rare earth modified Y-type molecular sieve: the rare earth content is 5wt%-20wt% in terms of rare earth oxide, for example, 5wt%, 6wt%, 9wt%, 10wt%, 10.4wt%, 12.4wt%, 14.3wt%, 15.6wt%, 16.1wt%, 16.2wt%, 19.8wt%, 20wt%, or a range consisting of any two of the above values, preferably 10-20wt%. The catalyst prepared using the composition under the aforementioned embodiment has better stability and metal utilization, can effectively protect the crystal structure of the catalyst, and inhibits the generation of polluted coke.

[0036] According to a preferred embodiment of the present invention, the crystallinity C / C0 of the rare earth modified Y-type molecular sieve is 50%-80%, for example, 50%, 55%, 58%, 60%, 62%, 63%, 65%, 70%, 80%, or a range consisting of any two of the above values, preferably 58%-65%. The catalyst prepared using the composition under the aforementioned embodiment has better stability and metal utilization, and when using it for catalytic cracking, it has excellent resistance to heavy metals and low coking effects.

[0037] According to a preferred embodiment of the present invention, the rare earth modified Y-type molecular sieve is obtained by modifying the Na-type Y molecular sieve, and preferably the modification treatment includes an ammonium sulfate exchange treatment step.

[0038] According to a particularly preferred embodiment of the present invention, the modification method comprises:

[0039] (a) exchanging the Na type Y molecular sieve with rare earth ions to obtain a rare earth ion slurry;

[0040] (b) adding a first precipitant to the rare earth ion slurry to cause a portion of the rare earth ions in the rare earth ion slurry to undergo a first precipitation to obtain a first precipitation slurry;

[0041] (c) subjecting the solid matter in the first precipitation slurry to a first ammonium sulfate exchange, a first water washing, and a first roasting to obtain a cross- and roasted molecular sieve dry powder;

[0042] (d) mixing the slurry containing the cross-linked and roasted molecular sieve dry powder with a second precipitant to cause a portion of the rare earth ions in the cross-linked and roasted molecular sieve dry powder to undergo a second precipitation, and then sequentially performing a second ammonium sulfate exchange, a second water washing, and optionally a heat treatment to obtain the rare earth modified Y-type molecular sieve.

[0043] In the present invention, the above-mentioned modification treatment avoids the formation of precipitation of free metal ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the supercage during the subsequent ammonium sulfate exchange and sodium reduction process. On the one hand, the purpose of reducing sulfate is achieved and the crystallinity and stability of the molecular sieve are improved. On the other hand, the utilization rate of the modified metal is improved, and the activity, stability and heavy oil conversion capacity of the catalyst prepared by the composition of the present invention can be significantly improved. At the same time, the independent phase rare earth material on the surface of the catalyst can preferentially generate vanadate rare earth with heavy metal V, thereby effectively protecting the molecular sieve crystal structure and inhibiting the generation of contaminated coke, thereby making the catalyst have the characteristics of high activity, good stability, strong heavy oil conversion capacity, excellent heavy metal resistance and low coke generation.

[0044] According to a preferred embodiment of the present invention, in step (a), the rare earth ion exchange process comprises: in the presence of water, the Na type Y molecular sieve and the rare earth source carry out the rare earth ion exchange; specifically, after the Na type Y molecular sieve and water are mixed, a rare earth source solution containing the rare earth source is added to carry out the rare earth ion exchange; wherein, preferably, the weight ratio of water to the Na type Y molecular sieve is 1.5-30:1, preferably 2-5:1; the solvent in the rare earth source solution is not particularly limited, and any good solvent that can dissolve the rare earth source can be used, and in the present invention, it is water, and the concentration of the rare earth source solution is generally 200-400g / L.

[0045] According to a preferred embodiment of the present invention, when rare earth ion exchange is performed, the rare earth source is selected from chlorates and / or nitrates containing at least one rare earth element, and preferably the rare earth element includes at least one of lanthanum, cerium and yttrium.

[0046] According to a preferred embodiment of the present invention, when rare earth ion exchange is performed, the Na-type Y molecular sieve is calculated on a dry basis, the rare earth source is calculated on a rare earth oxide basis, and the content of the rare earth source in the Na-type Y molecular sieve is 1-20% by weight, preferably 10-16% by weight.

[0047] According to a preferred embodiment of the present invention, during rare earth ion exchange, the rare earth ion exchange conditions include: a temperature of room temperature-180°C, preferably 50-80°C.

[0048] According to a preferred embodiment of the present invention, during rare earth ion exchange, the rare earth ion exchange conditions include: an exchange time of 0.3-3.5 h, preferably 0.5-1.5 h.

[0049] According to a preferred embodiment of the present invention, during rare earth ion exchange, the rare earth ion exchange conditions include: pH 2.8-6.5, preferably 3.5-4.5.

[0050] According to the present invention, those skilled in the art can understand that generally rare earth sources are acidic when dissolved in water. If the pH value is high at this time, an acidic substance such as dilute hydrochloric acid can be used to adjust the pH to the desired pH.

[0051] The amount of the first precipitant added in the present invention is determined according to the amount of rare earth ions in the rare earth ion exchange slurry. Preferably, in step (b), the amount of the first precipitant satisfies the molar ratio of the rare earth ions with a content of 1-4% by weight in the Na-type Y molecular sieve through the first precipitation, preferably satisfies the molar ratio of the rare earth ions with a content of 1.5-2.5% by weight in the Na-type Y molecular sieve through the first precipitation. The aforementioned implementation method is adopted to avoid the formation of precipitation of free RE ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the super cage during the subsequent ammonium sulfate exchange and sodium reduction process, thereby achieving the purpose of reducing sulfate, improving the crystallinity and stability of the molecular sieve, and at the same time improving the utilization rate of rare earths, forming an independent phase rare earth component resistant to heavy metals on the surface of the molecular sieve, and improving the heavy metal pollution resistance of the catalyst.

[0052] According to the present invention, as long as the purpose of the present invention can be achieved, in step (b), the conditions for the first precipitation are not particularly limited. Preferably, in step (b), the conditions for the first precipitation include: a temperature of 25-180°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.1-2h.

[0053] According to the present invention, it is understood that the first precipitation slurry contains solid matter and solvents such as water, and the method for obtaining the solid matter in the first precipitation slurry is not particularly limited, for example, it can be obtained by filtering, drying, etc.

[0054] According to the present invention, it can be understood that in step (c), the first ammonium sulfate exchange refers to the first ammonium sulfate exchange using ammonium sulfate. Preferably, in step (c), in the first ammonium sulfate exchange, the amount of ammonium sulfate used is 5-50% by weight of the weight of the Na-type Y molecular sieve, preferably 10-25% by weight.

[0055] According to the present invention, as long as the purpose of the present invention can be achieved, in step (c), the conditions for the first ammonium sulfate exchange are not particularly limited. Preferably, in step (c), the conditions for the first ammonium sulfate exchange include: a temperature of 20-85°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.1-2h.

[0056] According to a preferred embodiment of the present invention, the first ammonium sulfate exchange process comprises: performing a first ammonium sulfate exchange between the solid matter in the first precipitation slurry and an ammonium sulfate aqueous solution, more preferably, the concentration of the ammonium sulfate aqueous solution is 20-400 g / L, and further preferably, the concentration of the ammonium sulfate aqueous solution is 120-250 g / L.

[0057] The first water washing in step (c) of the present invention refers to washing the solid matter obtained by the first ammonium sulfate exchange with water. The method of the water washing is not particularly limited. For example, the solid matter obtained by the first ammonium sulfate exchange is eluted with water having a weight of 1-8 times, preferably 2-5 times, the weight of the Na-type Y molecular sieve.

[0058] According to a preferred embodiment of the present invention, in step (c), the first calcination condition includes: 100% water vapor atmosphere. The catalyst prepared using the composition under the above embodiment has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance and low coke formation when used.

[0059] According to a preferred embodiment of the present invention, in step (c), in step (c), the conditions of the first calcination include: a temperature of 400-700°C, preferably 500-650°C.

[0060] According to a preferred embodiment of the present invention, in step (c), in step (c), the conditions of the first calcination include: time is 0.1-5h, preferably 0.5-3h.

[0061] The slurry containing cross-linked and roasted molecular sieve dry powder in the present invention refers to a slurry obtained by mixing water and cross-linked and roasted molecular sieve dry powder. Preferably, in step (d), the weight ratio of water to cross-linked and roasted molecular sieve dry powder in the slurry containing cross-linked and roasted molecular sieve dry powder is 1.5-30:1, preferably 2-5:1.

[0062] According to a preferred embodiment of the present invention, the amount of the second precipitate satisfies the molar ratio of the rare earth ions in the cross-baked molecular sieve dry powder of 0.5-3 wt% through the second precipitate, preferably satisfies the molar ratio of the rare earth ions in the cross-baked molecular sieve dry powder of 1-2 wt% through the second precipitate. By adopting the above embodiment, the crystallinity and stability of the molecular sieve are improved, and the utilization rate of the rare earth is improved, and an independent phase rare earth component resistant to heavy metals is formed on the surface of the molecular sieve, thereby improving the anti-heavy metal pollution performance of the catalyst.

[0063] According to the present invention, as long as the purpose of the present invention can be achieved, in step (d), the conditions for the second precipitation are not particularly limited. Preferably, in step (d), the conditions for the second precipitation include: a temperature of 15-40°C, preferably 20-30°C; and / or a time of 0.1-5h, preferably 0.1-2h.

[0064] According to the present invention, it can be understood that in step (d), the second ammonium sulfate exchange refers to the use of ammonium sulfate for the second ammonium sulfate exchange. Preferably, in step (d), in the second ammonium sulfate exchange, the amount of ammonium sulfate used is 5-50% by weight of the cross-baked molecular sieve dry powder, preferably 10-25% by weight.

[0065] According to the present invention, as long as the purpose of the present invention can be achieved, in step (d), the conditions for the first ammonium sulfate exchange are not particularly limited. Preferably, in step (d), the conditions for the second ammonium sulfate exchange include: a temperature of 20-85°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.1-2h

[0066] According to a preferred embodiment of the present invention, the second ammonium sulfate exchange process is: subjecting the second precipitated product and the second ammonium sulfate aqueous solution to a second ammonium sulfate exchange, preferably the concentration of the second ammonium sulfate aqueous solution is 20-400 g / L, preferably 120-250 g / L.

[0067] The exchange process of the first ammonium sulfate exchange and the second ammonium sulfate exchange in the present invention can use tank exchange, belt exchange, or tank exchange and belt exchange can be carried out simultaneously. The present invention has no special limitation on this and will not be elaborated in detail in the present invention.

[0068] The second water washing in step (d) of the present invention refers to washing the solid matter obtained by the second ammonium sulfate exchange with water. The method of the water washing is not particularly limited. For example, the solid matter obtained by the second ammonium sulfate exchange is washed with water having a weight of 1 to 8 times, preferably 2 to 5 times, the weight of the cross-baked molecular sieve dry powder.

[0069] According to a preferred embodiment of the present invention, the heat treatment includes drying and a second calcination.

[0070] According to a preferred embodiment of the present invention, the second calcination condition includes: in an oxygen-containing atmosphere. By adopting the above embodiment, the crystallinity and stability of the molecular sieve are improved, and the utilization rate of rare earth is improved, and a heavy metal-resistant independent phase rare earth component is formed on the surface of the molecular sieve, thereby improving the heavy metal pollution resistance of the catalyst.

[0071] The oxygen-containing atmosphere in the present invention includes oxygen or air, and air is preferred in the present invention.

[0072] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a temperature of 400-700°C, preferably 450-650°C.

[0073] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a time of 0.1-10 h, preferably 0.5-5 h.

[0074] According to a preferred embodiment of the present invention, the Na-type Y molecular sieve includes at least one of NaY molecular sieve, NaHY molecular sieve, NaUSY molecular sieve, NaREHY molecular sieve and NaREUSY molecular sieve, preferably NaY molecular sieve.

[0075] According to the present invention, as long as the purpose of the present invention can be achieved, the specific types of the first precipitant and the second precipitant are not particularly limited. Preferably, the first precipitant and the second precipitant are each independently selected from ammonium compounds that can provide rare earth ions to produce anions of oxide precipitation precursors, preferably selected from one or more of ammonium oxalate, ammonium carbonate, ammonium bicarbonate and ammonia water.

[0076] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the matrix material is not particularly limited. Preferably, the matrix material includes clay; more preferably, the clay includes at least one of kaolin, halloysite, porphyrolith, diatomaceous earth and vesicle.

[0077] According to the present invention, the rare earth element source is selected from at least one of rare earth chloride, rare earth nitrate, rare earth oxide, rare earth carbonate, rare earth oxalate and rare earth acetate, preferably rare earth oxalate and / or rare earth oxide; wherein the rare earth metal elements in the rare earth element source are not particularly limited, for example, lanthanum and / or cerium.

[0078] According to a preferred embodiment of the present invention, the REUSY molecular sieve includes at least one of LaUSY molecular sieve, CeUSY molecular sieve and mixed rare earth USY molecular sieve; mixed rare earth USY molecular sieve refers to a molecular sieve containing at least two different types of rare earth elements, such as La and Ce. The catalyst prepared by the above composition has good resistance to heavy metal pollution, especially vanadium pollution. When it is used in the catalytic cracking process of high-vanadium heavy oil, the conversion rate of heavy oil is high, and the selectivity of dry gas and coke is low.

[0079] The REUSY used in the present invention has a RE2O3 content of 1.8wt%, specifically 1.44wt% La2O3 and 0.36wt% Ce2O3, to illustrate the advantages of the present invention, but the present invention is not limited to this.

[0080] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:

[0081] (1) homogenizing, shaping, and third calcining a slurry containing the catalytic cracking catalyst composition of the present invention to obtain a catalyst precursor;

[0082] (2) The catalyst precursor is modified by reducing sodium to obtain the catalytic cracking catalyst.

[0083] The catalyst prepared in the present invention has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance and low coke generation.

[0084] The slurry containing the composition for catalytic cracking catalyst of the present invention refers to a slurry obtained by mixing the composition of the present invention with whom. The mixing conditions are not particularly limited, and the mixing is preferably carried out at room temperature; preferably, the solid content of the slurry containing the composition for catalytic cracking catalyst is 25%-45wt%, preferably 35wt%-45wt%.

[0085] The molding method in step (1) of the present invention is not particularly limited, and is preferably spray molding, which is a conventional technical means in the art and will not be described in detail in the present invention.

[0086] According to a preferred embodiment of the present invention, the conditions of the third calcination include: a temperature of 400-550°C, preferably 450-500°C; and / or a time of 0.1-5h, preferably 0.1-2h

[0087] According to a preferred embodiment of the present invention, the sodium reduction modification method comprises: mixing a slurry containing a catalyst precursor with an ammonium salt to obtain a mixed solution, and then drying the solid matter in the mixed solution.

[0088] The catalyst precursor-containing slurry in the present invention refers to a slurry obtained by mixing a catalyst precursor and water. Preferably, the solid content of the catalyst precursor-containing slurry is 0.5 wt%-35 wt%, preferably 20 wt%-25 wt%.

[0089] According to a preferred embodiment of the present invention, the ammonium salt includes at least one of ammonium chloride, ammonium phosphate, diammonium hydrogen phosphate and diammonium dihydrogen phosphate, preferably ammonium chloride.

[0090] According to a preferred embodiment of the present invention, the weight ratio of the ammonium salt to the catalyst precursor is 2-10:100, preferably 3-6:100.

[0091] The third aspect of the present invention provides a catalytic cracking catalyst prepared by the method for preparing the catalytic cracking catalyst described in the second aspect of the present invention.

[0092] The catalyst of the present invention has the characteristics of high activity, good stability, strong heavy oil conversion ability, excellent heavy metal resistance and low coke generation.

[0093] According to a preferred embodiment of the present invention, in the catalytic cracking catalyst, the Na2O + The content is not more than 0.2wt%, preferably 0.1-0.18wt%.

[0094] The fourth aspect of the present invention provides use of the catalytic cracking catalyst of the present invention in catalytic cracking of heavy oil.

[0095] The catalyst of the present invention has the advantages of high activity, good stability and strong heavy oil conversion capacity when used in heavy oil catalytic cracking.

[0096] According to a preferred embodiment of the present invention, the catalytic cracking catalyst of the present invention is used in the catalytic cracking of high heavy metal heavy oil, and preferably the heavy metals include V and optionally Ni.

[0097] The catalyst of the present invention has good resistance to heavy metal pollution, especially vanadium pollution, and has the characteristics of high conversion rate, excellent heavy metal resistance and low coke generation when used in the catalytic cracking process of high-vanadium heavy oil.

[0098] The present invention will be described in detail below by way of examples. In the following examples, the analysis and evaluation methods used are:

[0099] 1. Unit cell constant (a0): X-ray diffraction method.

[0100] 2. Crystallinity (C / C0): X-ray diffraction method.

[0101] 3. Silicon to aluminum ratio: X-ray diffraction method.

[0102] 4.Na2O content: XRF fluorescence method.

[0103] 5.RE2O3 content: XRF fluorescence method.

[0104] 6. Sulfate content: XRF fluorescence method.

[0105] 7. Micro-reaction activity: The samples were pre-treated at 800℃ and 100% steam for different time periods. The reaction raw material was Dagang light diesel oil, the reaction temperature was 460℃, the reaction time was 70 seconds, the catalyst loading was 5.0 grams, the catalyst-oil weight ratio was 3.2, and the total conversion rate was taken as the micro-reaction activity.

[0106] 8.ACE heavy oil microreactor: The catalyst sample was pre-contaminated with V: 5000ppm and Ni: 3000ppm, and treated at 800℃, 100% water vapor for 5h, reaction temperature 530℃, catalyst-oil ratio of 5, and feedstock oil from Lanzhou Petrochemical's 3 million tons heavy oil catalytic unit.

[0107] In the following examples, the specifications of the raw materials used are as follows:

[0108] 1. NaY molecular sieve: NaY (silicon-aluminum ratio 5.1, crystallinity 95%), produced by Changting Catalyst Co., Ltd.

[0109] 2. Rare earth solution: Rare earth chloride and rare earth nitrate are both industrial products collected from the catalyst plant of Lanzhou Petrochemical Company.

[0110] 3.Ammonium sulfate, ammonium oxalate, ammonium carbonate, ammonium bicarbonate, ammonia water, urea, ammonium acetate, ammonium chloride, and ammonium nitrate are all analytical grade.

[0111] 4. Pseudo-boehmite (burn reduction 36.7wt%), kaolin (burn reduction 18.4wt%), halloysite (burn reduction 23.2wt%), porphyrylite (burn reduction 18.2wt%), diatomite (burn reduction 23.6wt%), vesicle stone (burn reduction 25.3wt%), REUSY (burn reduction 5.3%, RE content in terms of RE2O3 is 1.8wt% (specifically 1.44wt% La2O3, 0.36wt% Ce2O3), Na2O content is 1.2wt%, unit cell 24.56 angstroms) solids; aluminum sol, containing 22.6wt% of aluminum oxide; silica sol, containing 30.5wt% of silicon oxide, all are industrial qualified products.

[0112] Preparation Example 1-11

[0113] Preparation Example 1

[0114] Preparation of rare earth modified Y-type molecular sieve:

[0115] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.537 L (calculated as La2O3) of a 298 g / L LaCl3 aqueous solution (La 3+ 0.98 mol) was subjected to rare earth ion exchange (temperature was 80° C., time was 0.5 h) to obtain a rare earth ion exchange slurry; wherein the content of LaCl3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis was 16 wt%;

[0116] (b) Adding (32 g, 0.225 mol) ammonium oxalate monohydrate can make 2.4 wt% of La in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 80° C., time of 0.5 h) to obtain a first precipitation slurry;

[0117] (c) filtering and draining the first precipitated slurry, adding 0.833 L of 180 g / L ammonium sulfate aqueous solution, exchanging at 60° C. for 1 h, filtering and draining, adding 3 L of water for rinsing, and then calcining at 500° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-linked and roasted molecular sieve dry powder;

[0118] (d) After slurrying the above 1000 g (dry basis) cross-linked-roasted molecular sieve powder with 5 L of deionized water, 25.6 g (0.18 mol) of ammonium oxalate monohydrate was added to make 2 wt% of La in the above cross-linked-roasted molecular sieve powder. 3+ After the second precipitation (temperature is 25°C, time is 0.5h), 0.6L of 250g / L ammonium sulfate aqueous solution is added, exchanged at 80°C for 1.5h, filtered, drained, rinsed with 5L of water, dried, and calcined at 450°C in an air atmosphere for 2h to obtain a rare earth modified Y-type molecular sieve, recorded as Z1.

[0119] Preparation Example 2

[0120] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.358 L of La(NO3)3 solution (La2O3) with a concentration of 280 g / L was added. 3+ 0.615 mol) was subjected to rare earth ion exchange (temperature was 50° C., time was 1.5 h) to obtain a rare earth ion exchange slurry; wherein the content of La(NO3)3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis was 10 wt%;

[0121] (b) Adding (25.6 g, 0.18 mol) of ammonium oxalate monohydrate can make the 2 wt% La in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 50° C., time of 0.5 h) to obtain a first precipitation slurry;

[0122] (c) filtering the first precipitate slurry, draining it, adding 1.111 L of 180 g / L ammonium sulfate aqueous solution, exchanging it at 80° C. for 1 h, filtering it, draining it, adding 3 L of water for rinsing, and then calcining it at 600° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-calcined molecular sieve dry powder;

[0123] (d) The above-mentioned 1000g (dry basis weight) cross-linked and roasted molecular sieve powder was slurried with 5L of deionized water, and then (13g, 0.135mol) of ammonium carbonate was added to allow 1.5wt% of La3+ in the above-mentioned cross-linked and roasted molecular sieve powder to undergo a second precipitation (temperature of 25°C, time of 0.5h). Then, 1.666L of 120g / L ammonium sulfate aqueous solution was added, exchanged at 50°C for 1h, filtered, drained, rinsed with 2L of water, dried, and calcined at 500°C in an air atmosphere for 2.5h to obtain a rare earth modified Y-type molecular sieve, denoted as Z2.

[0124] Preparation Example 3

[0125] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.403 L of LaCl3 solution (LaCl3) with a concentration of 298 g / L (in terms of La2O3) was added. 3+ 0.74 mol) was subjected to rare earth ion exchange (temperature was 60° C., time was 1 h) to obtain a rare earth ion exchange slurry; wherein the content of LaCl3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis was 12.08 wt%;

[0126] (b) Adding (28 g, 0.197 mol) of ammonium oxalate monohydrate can make the 2.1 wt% La in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 60° C., time of 0.5 h) to obtain a first precipitation slurry;

[0127] (c) filtering the first precipitate slurry, draining it, adding 1.0 L of 180 g / L ammonium sulfate aqueous solution, exchanging it at 60° C. for 1.5 h, filtering it, draining it, adding 3 L of water for rinsing, and then calcining it at 630° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-linked and roasted molecular sieve dry powder;

[0128] (d) After slurrying the above 1000 g (dry basis) cross-linked and roasted molecular sieve powder with 5 L of deionized water, 15.4 g (0.11 mol) of ammonium oxalate monohydrate was added to make the La content in the cross-linked and roasted molecular sieve powder 1.2 wt %. 3+After the second precipitation (temperature is 25°C, time is 0.5h), 1.278L of 180g / L ammonium sulfate aqueous solution was added, exchanged at 50°C for 1h, filtered, drained, rinsed with 3L of water, dried, and calcined at 400°C in an air atmosphere for 2h to obtain a rare earth modified Y-type molecular sieve, recorded as Z3.

[0129] Preparation Example 4

[0130] (a) 1000 g (dry basis) of NaY molecular sieve was slurried with 5 L of deionized water, and then 0.43 L of a mixed RECl3 solution with a concentration of 326 g / L (in terms of RE2O3) (the weight ratio of Ce2O3 to La2O3 was 6:4; (RE 3+ 0.9287 mol) was subjected to metal ion exchange (temperature was 60° C., time was 1 h) to obtain a metal ion exchange slurry; wherein the content of RECl3 calculated as RE2O3 in the NaY molecular sieve calculated on a dry basis was 14 wt%;

[0131] (b) Adding (25.6 g, 0.18 mol) of ammonium oxalate monohydrate and then adding 5 mL of 28% industrial ammonia water can make 2.4 wt% of RE in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 60° C., time of 0.5 h) to obtain a first precipitation slurry;

[0132] (c) filtering the first precipitate slurry, draining it, adding 1.222 L of 180 g / L ammonium sulfate aqueous solution, exchanging it at 100° C. for 0.5 h, filtering it, draining it, adding 5 L of water for rinsing, and then calcining it at 600° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-linked and roasted molecular sieve dry powder;

[0133] (d) 1000 g (dry basis) of the cross-roasted molecular sieve powder was slurried with 5 L of deionized water, and then 18 g, 0.187 mol, of ammonium carbonate was added to make 1.8 wt% of the RE in the cross-roasted molecular sieve powder. 3+ After the second precipitation (temperature is 25°C, time is 0.5h), add 1L of 120g / L ammonium sulfate aqueous solution, exchange at 25°C for 1h, filter, drain, add 4L of water to rinse, dry, and calcine at 550°C in air atmosphere for 2h to obtain rare earth modified Y-type molecular sieve, recorded as Z4.

[0134] Preparation Example 5

[0135] The method of the preparation example is followed, except that:

[0136] In step (a), 0.537 L (calculated as La2O3) of a LaCl3 aqueous solution with a concentration of 298 g / L is replaced by 0.67 L (calculated as La2O3) of a LaCl3 aqueous solution with a concentration of 298 g / L, so that the content of LaCl3 calculated as La2O3 in the NaY molecular sieve on a dry basis is 20 wt%; the other conditions are the same, and a rare earth modified Y-type molecular sieve is obtained, recorded as Z5.

[0137] Preparation Example 6

[0138] The method of the preparation example is followed, except that:

[0139] In step (b), (32 g, 0.225 mol) ammonium oxalate monohydrate was replaced with (12.8 g, 0.09 mol) ammonium oxalate monohydrate, so that 1 wt% of La in the metal ion exchange slurry 3+ The first precipitation was carried out (temperature was 80°C, time was 0.5h); other conditions were the same, and a rare earth modified Y-type molecular sieve was obtained, which was recorded as Z6.

[0140] Preparation Example 7

[0141] The method of the preparation example is followed, except that:

[0142] In step (d), (25.6 g, 0.18 mol) of ammonium oxalate monohydrate was replaced with (6.4 g, 0.045 mol) of ammonium oxalate monohydrate, so that 0.5 wt% of La in the above cross-baked molecular sieve powder was 3+ The second precipitation was carried out (temperature was 25°C, time was 0.5h); other conditions were the same, and a rare earth modified Y-type molecular sieve was obtained, which was recorded as Z7.

[0143] Preparation Example 8

[0144] The method of the preparation example is followed, except that:

[0145] According to the method disclosed in CN200610087535.2, the modified molecular sieve DZ1 was prepared, namely,

[0146] Take 1000g (dry basis weight) of NaY molecular sieve, slurry it with 8L of deionized water, add 0.385L of RECl3 solution with a concentration of 312g / L (calculated as La2O3), add 240g of aluminum sulfate, exchange at 90°C for 1h, add 75g of ammonium bicarbonate, stir at constant temperature for 0.25h, filter, rinse with 5L of water, and then roast the filter cake at 600°C and 100% water vapor atmosphere for 2 hours to obtain a cross-baked molecular sieve dry powder;

[0147] Take 1000 g (dry basis weight) of the cross-baked molecular sieve powder, slurry it with 6 L of deionized water, add 300 g of ammonium sulfate, exchange it at 75°C for 1 h, filter it, rinse it with 6 L of water, and dry the filter cake to obtain a rare earth modified Y-type molecular sieve, recorded as DZ1.

[0148] Preparation Example 9

[0149] The method of Preparation Example 1 was followed, except that:

[0150] In step (d), ammonium oxalate monohydrate (32 g, 0.225 mol) was not added, and other conditions were the same to obtain a rare earth modified Y-type molecular sieve, which was recorded as DZ2.

[0151] Preparation Example 10

[0152] The method of Preparation Example 2 was followed, except that:

[0153] In step (b), no (25.6 g, 0.18 mol) ammonium oxalate monohydrate was added, and other conditions were the same, to obtain a rare earth modified Y-type molecular sieve, denoted as DZ3.

[0154] Preparation Example 11

[0155] The method of Preparation Example 4 was followed, except that:

[0156] In step (b), (25.6 g, 0.18 mol) of ammonium oxalate monohydrate and 5 mL of 28% industrial ammonia water were not added, and in step (d), (18 g, 0.187 mol) of ammonium carbonate was not added. The other conditions were the same, and a rare earth modified Y-type molecular sieve was obtained, which was recorded as DZ4.

[0157] The physical properties of the rare earth modified Y-type molecular sieves (Z1-Z7 and DZ1-DZ4) obtained in Preparation Examples 1-11 are shown in Table 1.

[0158] Table 1

[0159]

[0160] Test Example 1

[0161] The rare earth modified Y-type molecular sieves (Z1-Z7 and DZ1-DZ4) obtained in Preparation Examples 1-11 were subjected to a hydrothermal stability test.

[0162] The test conditions include: 100g (dry basis) of modified molecular sieves (Z1-Z7 and DZ1-DZ4) are respectively tableted and crushed into 20-40 mesh particles, and aged for 10 hours under 100% water vapor and 800°C in a fixed bed hydrothermal treatment device, and then the micro-activity index (MA) is measured on a catalytic cracking automatic micro-reaction activity assessor. The test results are shown in Table 2.

[0163] Table 2

[0164] Modified molecular sieve MA, wt% Preparation Example 1 Z1 71 Preparation Example 2 Z2 65 Preparation Example 3 Z3 69 Preparation Example 4 Z4 68 Preparation Example 5 Z5 69 Preparation Example 6 Z6 67 Preparation Example 7 Z7 65 Preparation Example 8 DZ1 60 Preparation Example 9 DZ2 61 Preparation Example 10 DZ3 59 Preparation Example 11 DZ4 60

[0165] Example 1

[0166] Preparation of catalytic cracking catalyst:

[0167] (1) Mixing the rare earth modified Y-type molecular sieve Z1, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, lanthanum oxalate and water at room temperature for 1 hour to obtain a slurry with a solid content of 32wt%; wherein the weight ratio of the rare earth modified Y-type molecular sieve Z1, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and lanthanum oxalate (calculated as RE2O3) is 20:15:7:18:38.5:1.5;

[0168] (2) The above slurry is homogenized, spray-formed, and calcined at 450° C. for 30 min to obtain a catalyst precursor, the catalyst precursor is mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and then mixed with ammonium chloride, filtered, washed with water 5 times, and dried at 100° C. for 12 h to obtain a catalytic cracking catalyst C1;

[0169] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0170] Among them, the Na in the catalytic cracking catalyst C1 is calculated as Na2O. + The content is 0.16wt%.

[0171] Example 2

[0172] Preparation of catalytic cracking catalyst:

[0173] (1) Mixing the rare earth modified Y-type molecular sieve Z2, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, lanthanum oxalate and water at room temperature for 1 hour to obtain a slurry with a solid content of 43wt%; wherein the weight ratio of the rare earth modified Y-type molecular sieve Z2, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and lanthanum oxalate (calculated as RE2O3) is 30:9:9:8:41.4:2.6;

[0174] (2) The above slurry is homogenized, spray-formed, and calcined at 470°C for 20 min to obtain a catalyst precursor. The catalyst precursor is mixed with water to form a slurry containing the catalyst precursor with a solid content of 25 wt%, which is then mixed with ammonium chloride, filtered, washed with 8 times of water, and dried at 120°C for 8 h to obtain a catalytic cracking catalyst C2.

[0175] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0176] Among them, the Na in the catalytic cracking catalyst C2 is calculated as Na2O. + The content is 0.11wt%.

[0177] Example 3

[0178] Preparation of catalytic cracking catalyst:

[0179] (1) Mixing the rare earth modified Y type molecular sieve Z3, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, cerium oxalate and water at room temperature for 1 hour to obtain a slurry with a solid content of 35wt%; wherein the weight ratio of the rare earth modified Y type molecular sieve Z3, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and cerium oxalate (calculated as RE2O3) is 26:12:8:15:38:1;

[0180] (2) The above slurry is sequentially homogenized, spray-formed, and calcined at 460°C for 35 min to obtain a catalyst precursor. The catalyst precursor is mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, which is then sequentially mixed with ammonium chloride, filtered, washed with 5 times of water, and dried at 110°C for 10 h to obtain a catalytic cracking catalyst C3.

[0181] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0182] Among them, the Na in the catalytic cracking catalyst C3 is calculated as Na2O. + The content is 0.15wt%.

[0183] Example 4

[0184] Preparation of catalytic cracking catalyst:

[0185] (1) Mixing the rare earth modified Y-type molecular sieve Z4, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, cerium oxalate and water at room temperature for 1 hour to obtain a slurry with a solid content of 39wt%; wherein the weight ratio of the rare earth modified Y-type molecular sieve Z4, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and cerium oxalate (calculated as RE2O3) is 24:11:7.5:12:43.7:1.8;

[0186] (2) The above slurry is sequentially homogenized, spray-formed, and calcined at 450°C for 30 min to obtain a catalyst precursor. The catalyst precursor is mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, which is then sequentially mixed with ammonium chloride, filtered, washed with water 6 times, and dried at 110°C for 10 h to obtain a catalytic cracking catalyst C4.

[0187] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0188] Among them, the Na2O in the catalytic cracking catalyst C4 is + The content is 0.12wt%.

[0189] Example 5

[0190] According to the method of implementing l, the difference is:

[0191] In step (1), the rare earth modified Y-type molecular sieve Z1 is replaced by the rare earth modified Y-type molecular sieve Z5, and the other conditions are the same, to obtain a catalytic cracking catalyst C5.

[0192] Example 6

[0193] According to the method of implementing l, the difference is:

[0194] In step (1), the rare earth modified Y-type molecular sieve Z1 is replaced by the rare earth modified Y-type molecular sieve Z6, and the other conditions are the same, to obtain a catalytic cracking catalyst C6.

[0195] Example 7

[0196] According to the method of implementing l, the difference is:

[0197] In step (1), the rare earth modified Y-type molecular sieve Z1 is replaced by the rare earth modified Y-type molecular sieve Z7, and the other conditions are the same, to obtain a catalytic cracking catalyst C7.

[0198] Comparative Example 1

[0199] (1) Mixing the rare earth modified Y-type molecular sieve DZ1, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, lanthanum chloride and water at room temperature for 1 hour to obtain a slurry with a solid content of 28wt%; wherein the weight ratio of the rare earth modified Y-type molecular sieve DZ1, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and lanthanum chloride (calculated as RE2O3) is 22:12:7:20:38.2:0.8;

[0200] (2) The slurry is homogenized, spray-formed, and calcined at 450° C. for 30 min to obtain a catalyst precursor, which is mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, which is then mixed with ammonium chloride, filtered, washed with water 4 times, and dried at 105° C. for 10 h to obtain a catalytic cracking catalyst DC1;

[0201] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0202] Among them, the Na+ content in the catalytic cracking catalyst DC1 is 0.28wt% in terms of Na2O.

[0203] Comparative Example 2

[0204] (1) Mixing the rare earth modified Y-type molecular sieve DZ2, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, cerium nitrate and water at room temperature for 1 hour to obtain a slurry with a solid content of 26wt%; wherein the weight ratio of the modified molecular sieve DZ2, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and cerium nitrate (calculated as RE2O3) is 22:10:6.5:22:39:0.5;

[0205] (2) The slurry is homogenized, spray-formed, and calcined at 470° C. for 30 min to obtain a catalyst precursor, which is mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, which is then mixed with ammonium chloride, filtered, washed with water 4 times, and dried at 120° C. for 10 h to obtain a catalytic cracking catalyst DC2;

[0206] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0207] Among them, the Na2O in the catalytic cracking catalyst DC2 is + The content is 0.23wt%.

[0208] Comparative Example 3

[0209] (1) Mixing the rare earth modified Y-type molecular sieve DZ3, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin, cerium chloride and water at room temperature for 1 hour to obtain a slurry with a solid content of 32wt%; wherein the weight ratio of the modified molecular sieve DZ3, REUSY molecular sieve, aluminum sol, acidified pseudo-boehmite, kaolin and cerium chloride (calculated as RE2O3) is 25:11:7.2:18:37.8:1;

[0210] (2) The slurry was homogenized, spray-formed, and calcined at 430° C. for 45 min to obtain a catalyst precursor, which was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, which was then mixed with ammonium chloride, filtered, washed with water 6 times, and dried at 100° C. for 10 h to obtain a catalytic cracking catalyst DC3;

[0211] The weight ratio of ammonium chloride to the slurry containing the catalyst precursor is 5:100.

[0212] Among them, the Na2O in the catalytic cracking catalyst DC3 is + The content is 0.25wt%.

[0213] Comparative Example 4

[0214] The method of Example 1 is different from that of Example 1:

[0215] The rare earth modified Y-type molecular sieve Z1 is replaced by the rare earth modified Y-type molecular sieve DZ4, and the other conditions are the same to obtain the catalytic cracking catalyst DC4.

[0216] Among them, the Na2O in the catalytic cracking catalyst DC4 is + The content is 0.23wt%.

[0217] Test Example 2

[0218] The catalytic cracking catalysts (C1-C7 and DC1-DC4) prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to a reaction performance test, and the test conditions included: the above catalytic cracking catalysts (C1-C7 and DC1-DC4) were contaminated with V: 5000ppm and Ni: 3000ppm, respectively, and treated at 800°C and 100% water vapor for 5h, and then added to the ACE heavy oil microreactor with the feed oil of the 3 million ton heavy oil catalytic unit of Lanzhou Petrochemical, and catalytic cracking was carried out (temperature of 530°C; catalyst-oil ratio of 5) to obtain catalytic cracking products; wherein the catalytic cracking products include: dry gas, liquefied gas, gasoline, diesel, heavy oil and coke, wherein the weight ratio of the catalytic cracking catalyst to the feed oil of the 3 million ton heavy oil catalytic unit of Lanzhou Petrochemical is 5:1, and the test results are shown in Tables 3 and 4.

[0219] Table 3

[0220]

[0221] Table 4

[0222]

[0223] Note: 1-refers to the conversion rate of the raw oil of the 3 million heavy oil catalytic unit of Lanzhou Petrochemical, that is, 100-diesel-heavy oil; 2-refers to the sum of the yields of liquefied gas, gasoline and diesel; 3-refers to [coke*(100-conversion rate)] / conversion rate

[0224] It can be seen from the test results in Table 3 and Table 4 that, compared with Comparative Examples 1-4, the catalytic cracking catalysts prepared in Examples 1-7 have excellent resistance to heavy metal pollution and coke selectivity, that is, they have higher conversion rate, total liquid yield and lower coke yield and coke generation factor.

[0225] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalytic cracking catalyst composition, characterized in that: The composition comprises: a rare earth modified Y-type molecular sieve, a binder, a matrix material, a rare earth element source, and optionally a REUSY molecular sieve; Among them, in the rare earth modified Y-type molecular sieve, SO4 2- The content is not more than 1wt%.

2. The composition according to claim 1, wherein The rare earth element source is calculated based on the weight of rare earth oxide, and the composition comprises: 15-35 weight % of rare earth modified Y-type molecular sieve, 0-20 weight % of REUSY molecular sieve, 6-30 weight % of binder, 30-55 weight % of matrix material, and 0.5-4 weight % of rare earth element source; Preferably, the rare earth element source is calculated based on the weight of rare earth oxide, and the composition comprises: 18-27 wt % of rare earth modified Y-type molecular sieve, 8-15 wt % of REUSY molecular sieve, 8-25 wt % of binder, 35-45 wt % of matrix material, and 0.8-3 wt % of rare earth element source.

3. The composition according to claim 1 or 2, wherein In the rare earth modified Y-type molecular sieve: SO4 2- The content of is not more than 0.5wt%; and / or The sodium content is not more than 1.5wt% calculated as Na2O, preferably 0.5wt%-1.2wt%; and / or The rare earth content is 5wt%-20wt% calculated as rare earth oxide, preferably 10-20wt%; and / or The crystallinity C / C0 of the rare earth modified Y-type molecular sieve is 50%-80%, preferably 58%-65%.

4. The composition according to any one of claims 1 to 3, wherein The rare earth modified Y-type molecular sieve is obtained by modifying the Na-type Y molecular sieve, and preferably the modification treatment includes an ammonium sulfate exchange treatment step; Preferably, the modification method comprises: (a) exchanging the Na type Y molecular sieve with rare earth ions to obtain a rare earth ion slurry; (b) adding a first precipitant to the rare earth ion slurry to cause a portion of the rare earth ions in the rare earth ion slurry to undergo a first precipitation to obtain a first precipitation slurry; (c) subjecting the solid matter in the first precipitation slurry to a first ammonium sulfate exchange, a first water washing, and a first roasting to obtain a cross- and roasted molecular sieve dry powder; (d) mixing the slurry containing the cross-linked and roasted molecular sieve dry powder with a second precipitant to cause a portion of the rare earth ions in the cross-linked and roasted molecular sieve dry powder to undergo a second precipitation, and then sequentially performing a second ammonium sulfate exchange, a second water washing, and optionally a heat treatment to obtain the rare earth modified Y-type molecular sieve.

5. The composition according to claim 4, wherein In step (a), the rare earth ion exchange process comprises: in the presence of water, the Na-type Y molecular sieve is subjected to the rare earth ion exchange with the rare earth source; Preferably, the rare earth source is selected from chlorates and / or nitrates containing at least one rare earth element, preferably the rare earth element comprises at least one of lanthanum, cerium and yttrium; and / or The Na-type Y molecular sieve is calculated on a dry basis, and the rare earth source is calculated on a rare earth oxide basis, and the content of the rare earth source in the Na-type Y molecular sieve is 1-20 wt %, preferably 10-16 wt %; and / or The weight ratio of water to Na-type Y molecular sieve is 1.5-30:1, preferably 2-5:1; and / or The rare earth ion exchange conditions include: a temperature of room temperature-180°C, preferably 50-80°C; and / or an exchange time of 0.3-3.5h, preferably 0.5-1.5h; and / or a pH of 2.8-6.5, preferably 3.5-4.

5.

6. The composition according to claim 4 or 5, wherein In step (b), the amount of the first precipitant is such that the content of rare earth ions in the Na-type Y molecular sieve is 1-4 wt% by molar ratio after the first precipitation, preferably such that the content of rare earth ions in the Na-type Y molecular sieve is 1.5-2.5 wt% by molar ratio after the first precipitation; and / or In step (b), the conditions for the first precipitation include: a temperature of 25-180° C., preferably 50-80° C.; and / or a time of 0.1-5 h, preferably 0.1-2 h.

7. The composition according to any one of claims 4 to 6, wherein In step (c), in the first ammonium sulfate exchange, the amount of ammonium sulfate used is 5-50% by weight, preferably 10-25% by weight, of the weight of the Na-type Y molecular sieve; and / or In step (c), the conditions for the first ammonium sulfate exchange include: a temperature of 20-85° C., preferably 50-80° C.; and / or a time of 0.1-5 h, preferably 0.1-2 h; Preferably, the first ammonium sulfate exchange process comprises: performing a first ammonium sulfate exchange between the solid matter in the first precipitation slurry and an ammonium sulfate aqueous solution, wherein the concentration of the ammonium sulfate aqueous solution is preferably 20-400 g / L, preferably 120-250 g / L; and / or In step (c), the first calcination conditions include: 100% water vapor atmosphere; and / or, a temperature of 400-700° C., preferably 500-650° C.; and / or, a time of 0.1-5 h, preferably 0.5-3 h.

8. The composition according to any one of claims 4 to 7, wherein In step (d), in the slurry containing cross-linked and roasted molecular sieve dry powder, the weight ratio of water to cross-linked and roasted molecular sieve dry powder is 1.5-30:1, preferably 2-5:1; and / or In step (d), the amount of the second precipitate satisfies the molar ratio of the rare earth ions in the cross-roasted molecular sieve dry powder to 0.5-3 wt % through the second precipitate, preferably satisfies the molar ratio of the rare earth ions in the cross-roasted molecular sieve dry powder to 1-2 wt % through the second precipitate; and / or In step (d), the conditions of the second precipitation include: a temperature of 15-40°C, preferably 20-30°C; and / or a time of 0.1-5h, preferably 0.1-2h; and / or In step (d), in the second ammonium sulfate exchange, the amount of ammonium sulfate used is 5-50% by weight, preferably 10-25% by weight, of the weight of the cross-baked molecular sieve dry powder; and / or In step (d), the conditions for the second ammonium sulfate exchange include: a temperature of 20-85° C., preferably 50-80° C.; and / or a time of 0.1-5 h, preferably 0.1-2 h; Preferably, the second ammonium sulfate exchange process is: exchanging the second precipitated product with the second ammonium sulfate aqueous solution, preferably the concentration of the second ammonium sulfate aqueous solution is 20-400 g / L, preferably 120-250 g / L; and / or The heat treatment includes drying and second calcination. Preferably, the conditions of the second calcination include: oxygen-containing atmosphere; and / or a temperature of 400-700°C, preferably 450-650°C; and / or a time of 0.1-10h, preferably 0.5-5h.

9. The composition according to any one of claims 4 to 8, wherein The Na-type Y molecular sieve includes at least one of NaY molecular sieve, NaHY molecular sieve, NaUSY molecular sieve, NaREHY molecular sieve and NaREUSY molecular sieve; and / or The first precipitant and the second precipitant are each independently selected from ammonium compounds that can provide rare earth ions with anions that generate oxide precipitation precursors, preferably selected from one or more of ammonium oxalate, ammonium carbonate, ammonium bicarbonate and ammonia water.

10. The composition according to any one of claims 1 to 9, wherein The binder comprises at least one of aluminum sol, acidified pseudo-boehmite, acidic silica sol and phosphate aluminum sol; and / or The matrix material comprises clay, preferably the clay comprises at least one of kaolin, halloysite, porphyrite, diatomite and vesicle; and / or The rare earth element source is selected from at least one of rare earth chloride, rare earth nitrate, rare earth oxide, rare earth carbonate, rare earth oxalate and rare earth acetate, preferably rare earth oxalate and / or rare earth oxide; and / or The REUSY molecular sieve includes at least one of a LaUSY molecular sieve, a CeUSY molecular sieve and a mixed rare earth USY molecular sieve.

11. A method for preparing a catalytic cracking catalyst, characterized in that: The preparation method comprises: (1) homogenizing, shaping, and third calcining a slurry containing the catalytic cracking catalyst composition according to any one of claims 1 to 10 to obtain a catalyst precursor; (2) The catalyst precursor is modified by reducing sodium to obtain the catalytic cracking catalyst.

12. The preparation method according to claim 11, wherein The solid content of the slurry containing the catalytic cracking catalyst composition is 25%-45wt%, preferably 35wt%-45wt%; and / or The conditions of the third calcination include: a temperature of 400-550° C., preferably 450-500° C.; and / or a time of 0.1-5 h, preferably 0.1-2 h; and / or The sodium reduction modification method comprises: mixing a slurry containing a catalyst precursor with an ammonium salt to obtain a mixed liquid, and then drying the solid matter in the mixed liquid; Preferably, the ammonium salt comprises at least one of ammonium chloride, ammonium phosphate, diammonium hydrogen phosphate and diammonium dihydrogen phosphate, preferably ammonium chloride; and / or The weight ratio of the ammonium salt to the catalyst precursor is 2-10:100, preferably 3-6:100; and / or The solid content of the catalyst precursor-containing slurry is 0.5 wt%-35 wt%, preferably 20 wt%-25 wt%.

13. A catalytic cracking catalyst prepared by the preparation method according to claim 11 or 12; Preferably, in the catalytic cracking catalyst, the Na2O-based + The content is not more than 0.2wt%, preferably 0.1-0.18wt%.

14. Use of the catalytic cracking catalyst according to claim 13 in catalytic cracking of heavy oil, preferably in catalytic cracking of high heavy metal heavy oil, preferably the heavy metal comprises V and optionally Ni.

Citation Information

Patent Citations

  • Prepn process of REY molecular sieve

    CN101088613A

  • Heavy oil catalytic cracking catalyst

    CN101385983A

  • Silicon-carrier lanthanum carbonate catalytic cracking microspherical vanadium-resistant aid and preparation method thereof

    CN102228838A

  • A metal trapping agent, its preparation method and application, and a catalytic cracking method

    CN103785428B

  • Method of ion exchange on zeolites

    CN103946160B